SDHC phaeochromocytoma and paraganglioma: A UK‐wide case series. (24th September 2021) - Williams, Sophie T.; Chatzikyriakou, Prodromos; Carroll, Paul V.; McGowan, Barbara M.; Velusamy, Anand; White, Gemma; Obholzer, Rupert; Akker, Scott; Tufton, Nicola; Casey, Ruth T.; Maher, Eamonn R.; Park, Soo‐Mi; et al.
Abstract: Objective: Phaeochromocytomas and paragangliomas (PPGL) are rare, but strongly heritable tumours. Variants in succinate dehydrogenase (SDH) subunits are identified in approximately 25% of cases. However, clinical and genetic information of patients with SDHC variants are underreported. Design: This retrospective case series collated data from 18 UK Genetics and Endocrinology departments. Patients: Both asymptomatic and disease‐affected patients with confirmed SDHC germline variants are included. Measurements: Clinical data including tumour type and location, surveillance outcomes and interventions, SDHC genetic variant assessment, interpretation, and tumour risk calculation. Results: We report 91 SDHC cases, 46 probands and 45 non‐probands. Fifty‐one cases were disease‐affected. Median age at genetic diagnosis was 43 years (range: 11–79). Twenty‐four SDHC germline variants were identified including six novel variants. Head and neck paraganglioma (HNPGL, n = 30, 65.2%), extra‐adrenal paraganglioma (EAPGL, n = 13, 28.2%) and phaeochromocytomas (PCC) ( n = 3, 6.5%) were present. One case had multiple PPGLs. Malignant disease was reported in 19.6% (9/46). Eight cases had non‐PPGL SDHC‐associated tumours, six gastrointestinal stromal tumours (GIST) and two renal cell cancers (RCC). Cumulative tumour risk (95% CI) at age 60 years was 0.94 (CI: 0.79–0.99) in probands, and 0.16 (CI: 0–0.31) in non‐probands, respectively. Conclusions: This study describes the largest cohort of 91 SDHC patients worldwide. We confirm disease‐affected SDHC variant cases develop isolated HNPGL disease in nearly 2/3 of patients, EAPGL and PCC in 1/3, with an increased risk of GIST and RCC. One fifth developed malignant disease, requiring comprehensive lifelong tumour screening and surveillance.